2019
DOI: 10.1111/1750-3841.14432
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion of a Curcuminoid‐Enriched Oat Fiber‐Corn‐Based Snack Product

Abstract: Extruded snack products were made from an oat fiber-corn flour matrix fortified with 1.5% (w/w) curcuminoids (750 mg curcuminoids/100 g) to improve the solubility and stability of curcuminoids. The effects of extruder feed moisture content (21%, 28%, and 35%) and screw speed (200 and 300 rpm) on the extrusion parameters and physical properties of final snacks were investigated. Curcuminoids lost during extrusion and curcuminoids loss during subsequent drying of extrudates were analyzed, to separate the losses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…Color is an important physical characteristic that influences consumers' acceptance for food (Sayanjali et al., 2019). Table 1 shows the color parameters of the FER grains with different microwave power treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Color is an important physical characteristic that influences consumers' acceptance for food (Sayanjali et al., 2019). Table 1 shows the color parameters of the FER grains with different microwave power treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Color is an important physical characteristic that influences consumers' acceptance for food (Sayanjali et al, 2019).…”
Section: Color Of Fermentioning
confidence: 99%
“…To increase consumer acceptability of extruded snacks containing mushroom, flavor addition to the extruded snacks will be evaluated in the future. There have been various studies evaluating quality of extruded products processed under a constant barrel temperature (Ma & Ryu, ; Sayanjali et al, ; Sumargo et al, ). However, barrel temperatures have been shown to affect quality of extrudates (Wan et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that insoluble fiber decreases the proportion of starchy material and reduces the viscosity for expansion. The fiber also binds to water during extrusion, therefore reducing their availability for expansion [27,28] .…”
Section: Apparent Density Expansion Index and Texture Analysismentioning
confidence: 99%
“…The incorporation of fibers in extrudates limits their expansion The effect of extrusion processing on the physicochemical and antioxidant properties of fermented and non-fermented Jabuticaba pomace and reduces their crunchiness [30] . Both the hardness and the crunchiness of the extrudates are associated to the expansion and cellular structure of the product [28] . Therefore, an extrudate with low expansion results in a product with reduced crunchiness and high hardness.…”
Section: Apparent Density Expansion Index and Texture Analysismentioning
confidence: 99%